Effects of different background colors on adult spawning, egg hatchability, and larval survival of zebrafish (Danio rerio) - Marwin B. Dela Cruz (Journal of Fisheries, 2020)
Background color has significant effects on the reproductive and survival performance of fish species. While zebrafish (Danio rerio) is a popular species in laboratory and recreational aquaculture, very little has been known about its background color preference. Thus, this study evaluated the effects of different colors of aquaria on the spawning, hatching, and survival of this species. The study found that zebrafish do not have color preference for spawning. Though red and black backgrounds are statistically comparable, these colors showed significantly higher (P < 0.05) hatching and survival rates than other colors used in this study. Furthermore, performance of red was higher than black but it was not statistically significant. This study reveals that, among all colors evaluated, red is the most suitable for hatching of zebrafish eggs and survival of its larvae whereas, yellow and transparent should be avoided.